Exploring the roles of heritage museums in promoting intangible and tangible heritage in Kelantan - Norashikin Abdul Karim,; Siti Norlizaiha Harun,; Salwa Ayob, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Malaysia is committed to preserving heritage buildings into heritage museums for documentation and education. Heritage museums could promote tangible and intangible heritage through its interior appearances and exhibitions. The Jahar Palace of Kelantan is a heritage palace that remains intact, and its space functions are still recognised even after being converted into a museum. This palace promotes intangible heritage and plays the role of the Kelantan Royal Traditions and Customs Museum. Four essential components that need to be focused by heritage museums are preserving the building’s history, preserving the authenticity of the historic building, preserving the initial space function, and preserving the exhibition contents of space. This paper aims to raise awareness of the value of tangible and intangible heritage in heritage museums. This paper is qualitative research adapting the case study method. Observation on-site, measured drawings, documents study and site tour, were some of the approaches that have been applied to obtain the data. The photographic mapping technique using the historic photograph, sketches, drawings, books, and journals were applied to investigate the origin of the building space. The data was analysed and presented in table form to differentiate the pattern of findings. The results indicated that the roles of heritage museums are required not only to display historical object but also to communicate the significance of the historic building. In other sense, the display of the building and its contents would indirectly act as an exhibit resource in promoting intangible and tangible heritage.